2017
DOI: 10.1177/1049909117745292
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Edmonton Symptom Assessment System for the Assessment of Depression in Patients With Cancer: A Systematic Review and Meta-Analysis

Abstract: We suggest that an ESAS-D ≥ 4 could be used to detect possible cases of depression in patients with cancer. Registration: Our study protocol was registered with the International Prospective Register of Systematic Reviews on October 4, 2016, and was last updated on January 11, 2017 (registration number CRD42016048288).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The ESAS-D cutoff that best balanced specificity and sensitivity for this purpose was ≥2. This result contrasts with a systematic review and meta-analysis, which concluded that an ESAS-D cutoff score of ≥4 is best for detecting depression (sensitivity 53% [95% CI: 38%-67%] and specificity 90% [95% CI: 82%-94%]) (Boonyathee et al 2018). This discrepancy may be due to the possibility that the best cutoff may be population specific.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The ESAS-D cutoff that best balanced specificity and sensitivity for this purpose was ≥2. This result contrasts with a systematic review and meta-analysis, which concluded that an ESAS-D cutoff score of ≥4 is best for detecting depression (sensitivity 53% [95% CI: 38%-67%] and specificity 90% [95% CI: 82%-94%]) (Boonyathee et al 2018). This discrepancy may be due to the possibility that the best cutoff may be population specific.…”
Section: Discussionmentioning
confidence: 57%
“…This provides further support for the need to replicate the current findings in other populations, including individuals who live in different countries. Third, although the power analysis conducted indicated that a sample size of 49 would be adequate for estimating the sensitivity and specificity of the ESAS-D item in the current study, this sample size is lower than that used by many other studies in this area, which have sample sizes that can range from 146 to as many as 969 (Boonyathee et al 2018). Another limitation pertains to the relatively high dropout rate, which was largely due to functional decline stemming from natural prognosis of cancer, which prevented full adherence to the protocol.…”
Section: Limitationsmentioning
confidence: 76%
“…This same cut-off level has also been shown to be useful in detecting clinical depression defined by standardized questionnaires among patients with cancer. 30 According to the logistic regression analysis, the relation between ESAS depression scores is not affected by subjects’ characteristics or other ESAS items. Based on the current results, we suggest that in patients scoring 0 on the ESAS depression question, there is probably no need for further evaluation of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The responses on the ESAS (0 = absent to 10 = extremely severe) for each symptom were grouped into four categories according to the responses: absent (0), mild (1, 2, 3), moderate (4, 5, 6), and severe (7, 8, 9, 10) [ 21 ]. We compared symptom severity between the curative intent group and the palliative intent group (curative intent group treatment aimed to achieve complete remission and prevent a recurrence, while the palliative intent group focused on no cure but simply decreasing tumor burden and prolonging life expectancy) [ 22 ] by Chi-Square tests.…”
Section: Methodsmentioning
confidence: 99%